The Capacity of Lignin to Enhance the Phthorimaea opercullela Granulovirus (PhopGV) Stability in Laboratory Condition - Bhattarai, Shiva Shankar; Aryal, Sunil; Thapa, Resham Bahadur (International Journal of Applied Sciences and Biotechnology, 2015)
The lab persistence of Phthorimaea opercullela granulovirus (PhopGV) with and without lignin for egg bioassay with different five virus concentrations (lab experiment- 60, 10, 1.67, 0.28 and 0.046 LE/l 20- 0.015432 LE/l ) to determine the inactivation curve under artificial UVlight, assess the effect and verify the protective capacity of lignin with PhopGV for virus preparations suspensions of raw PhopGV alone and mixed with lignin (1%) used as UV protectants was conducted in simply completely randomised design in the laboratory condition. The LC50 value for PhopGV in lab condition was 1x10-3 LE/l with the slope of the probit regression line 0.51. Similarly, half inactivation speed with lignin was 4.58 days compared to 0.559 days without lignin in lab condition. Inactivation speed was decreased by 87.8 % in case of lignin applied in lab condition. So, the suppression of PTM with virus combined with lignin gave cost effective measures through the use of low dosages. In lab experiment, the control mortality of 19.6 % was probable for all the controls of lignin present and absent. This revealed that there was no effect of lignin alone on target insects’ survival. Int J Appl Sci Biotechnol, Vol 3(2): 256-260 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12481